ANALISIS RAGAM PRODUK, HARGA, DAN KUALITAS PRODUK TERHADAPA MINAT BELI KONSUMEN UNTUK UMKM ECENG GONDOK DI KOTA SURABAYA - Salma Mutia Hanifah (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
In these millennials era, business is the great opportunity to be able to produce profits, one of its namely entrepreneurship. Entrepreneurship work to increase a series of competition from various aspects with the aim of increasing competitiveness, providing employment, reducing unemployment and poverty. Entrepreneurship is mediated as